Pengaruh Leverage, dan Ukuran Perusahaan Terhadap Kinerja Keuangan pada Sektor Property & Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2021 - Agatha, Gabriella (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The achievement of this study is to investigate the effect of the use of leverage and company size on the financial performance of companies in the property and real estate sector that have gone public and are listed on the Indonesian Stock Exchange (IDX) between 2020 and 2021. In order to collect a sample, the authors apply purposive sampling method which produces 32 business entities as research samples. Leverage testing uses the ratio of debt to assets (Debt to Asset Ratio), while the dimensions of the company are measured by the logarithm of total assets (Ln of Total Assets). To evaluate company performance, the Return on Assets metric is used. The results of the study show that the use of leverage has a negative influence on the financial performance of business entities in the listed property and real estate sector. However, the financial achievements of companies in the same sector have not been significantly influenced by the dimensions of the company. Keywords: Company's Financial Performance, Company’s Size, Leverage